High‐Performance Stretchable Thermoelectric Generator for Self‐Powered Wearable Electronics. Issue 12 (17th February 2023) - Fan, Wusheng; An, Zijian; Liu, Feng; Gao, Ziheng; Zhang, Min; Fu, Chenguang; Zhu, Tiejun; Liu, Qingjun; Zhao, Xinbing
Abstract: Wearable thermoelectric generators (TEGs), which can convert human body heat to electricity, provide a promising solution for self‐powered wearable electronics. However, their power densities still need to be improved aiming at broad practical applications. Here, a stretchable TEG that achieves comfortable wearability and outstanding output performance simultaneously is reported. When worn on the forehead at an ambient temperature of 15 °C, the stretchable TEG exhibits excellent power densities with a maximum value of 13.8 µW cm −2 under the breezeless condition, and even as high as 71.8 µW cm −2 at an air speed of 2 m s −1, being one of the highest values for wearable TEGs. Furthermore, this study demonstrates that this stretchable TEG can effectively power a commercial light‐emitting diode and stably drive an electrocardiogram module in real‐time without the assistance of any additional power supply. These results highlight the great potential of these stretchable TEGs for power generation applications. Abstract : A stretchable thermoelectric generator (TEG) is fabricated, which exhibits both outstanding output performance and comfortable wearability for human body heat harvesting. The stretchable TEGs are enough for driving an electrocardiogram module in real time without the assistance of an additional power supply.